(untitled) (The Journal of Psychology and Sociology, 2021)
The requirement for parental consent for conducting abortion for minors has always been a highly debatable and controversial ethical issue. In terms of ethical debate, there are manifolded ‘pros’ and ‘cons’ of liberal legislation on abortion for the underage girls. Worldwide experience has revealed that the variations in the laws as well as the arguments for and against abortion for teenagers differ depending on geographical location, ethnicity, religion, and cultural peculiarities. This paper juxtaposes arguments in favor for and against parental consent, as well as neutral arguments neither for nor against, narrowing down the issue to the context of Kazakhstan. At the same time, the paper also uses ethical stances of virtuous and utilitarian aspects for argumentative purposes and touching upon the aspects of morality. In conclusion, the paper argues in favor for mitigating the access for underage girls in Kazakhstan on a legislative level and suggests that Kazakhstan should reconsider as well as readapt its regulation and laws on abortion in order to maintain health, happiness, utility, and reproductive abilities of future-to-be mothers. Thus, a law mitigating the access to abortion for youngsters could make a huge positive impact for both underage girls as well as the society to reach an agreeable consensus between the two. Key words: abortion, Kazakhstan, minors, parental consent, ethics.